Respon Peserta Didik dalam Memecahkan Masalah Matematika Berdasarkan Taksonomi SOLO (Structure of Observed Learning Outcome) - Anisa Fitri; Naning Kurniawati; Zaki Mubaroh (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2021)
In mathematics learning cannot be separated from problems. A problem in mathematics is defined as a problem that does not have a routine procedure to do it. A student will consider a question to be a problem if students have difficulty finding solutions to problems or questions using the knowledge they have. One way to identify the appropriateness of student responses to math problems or problems is the SOLO taxonomy (Structure of Observed Learning Outcomes). SOLO taxonomy is used to measure the quality of students 'answers to a problem based on the complexity of students' understanding or answers to a given problem. This study discusses student responses to math problems. Not only that, this study also discusses how to describe the structure of cognitive complexity or student responses from existing levels based on five stages, namely Prestructural, Unistructural, Multistructural, Relational, and Extended Abstract. The results of the study concluded that each student has a different problem solving response. Overall subject 1 can solve problem solving problems at the multistuctural level. Furthermore, subject 2 can solve problem solving problems at Unistrustural level. Then the latter, the subject cannot solve the problem solving as a whole so that it is at the Prestuctural level. This condition is the goal of this study, where by knowing the student's response to solving math problems, steps can be taken for the success of the learning process.